A rare location of tricuspid papillary fibroelastoma: a case report - S. A. Chepurnenko; G. V. Shavkuta; M. S. Chepurnenko (Кардиоваскулярная терапия и профилактика)
Introduction. Papillary fibroelastoma is the second most common benign cardiac tumor after myxoma. Unlike myxoma; which is mainly located in the fossa ovalis area and is a hamartoma by origin; fibroelastoma originates from endocardial cells and is therefore located on the heart valves; mainly on the aortic one (44%). It is found on the tricuspid valve in 15% of cases. Fibroelastoma may be asymptomatic; but in some cases; it leads to embolism in the form of myocardial infarction or stroke if located on the aortic valve; or pulmonary embolism if located on the tricuspid valve.Brief description. A case of a rare tricuspid fibroelastoma in a 67-year-old woman is presented. The patient sought help due to frequent blood pressure increase against the background of the therapy she was taking. She was examined in accordance with the current clinical guidelines on hypertension in adults. Echocardiography revealed mass in the right atrium. Intraoperative assessment revealed the mass of 1;6´1;5´1;3 cm with a villous surface and a loose; jellylike consistency; which is attached to the anterior tricuspid leaflet by a pedicle. Histological analysis identified papillary fibroelastoma.Conclusion. Differential diagnostics of papillary fibroelastoma is extensive and includes benign (myxoma; fibroma); malignant (lymphoma; sarcoma) and metastatic heart tumors. Valvular vegetations; Lambl's excrescences; cysts; thrombus; fenestration and artifacts should be also ruled out. Cardiac ultrasound does not make it possible to determine the mass origin. Only histological analysis revealed that it was papillary fibroelastoma. The clinical example emphasizes the importance of examining each patient in accordance with related clinical guidelines. This allows for timely detection and prevention of severe embolic complications; usually characteristic of fibroelastoma.